ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII)TAHUN 2012 – 2017 - Varaulizza, Ajeng Vashqie (Equator Journal of Management and Entrepreneurship (EJME), 2019)
AbstractTo begin with, stocks are one of the interested investments in Indonesia while one of them aresharia stocks which is based on Islamic law. As an investment alternative based on Islamic sharia,the existence of sharia stocks in the Jakarta Islamic Index (JII) displays the growth value anuallycompared to common stocks’ values. The sampling method is purposive sampling. Meanwhile,the data would be analysed by multiple regression analysis using SPSS 17. To conclude, there arefour results : (1) the liquidy ratio (current ratio) affects significantly towards stocks return; (2) thesolvency ratio (depth to equity ratio) affects significantly towards stocks; (3) the profitability ratio(return on asset) affects significantly towards stocks return; and (4) the market ratio (price earningratio) does not have significant impact on stocks return and the size of companies as controllingvariable in the Jakarta Islamic Index (JII).Keywords : Financial Ratio, Size of Company, Stocks Return, The Jakarta Islamic Index (JII)